2016
DOI: 10.1364/oe.24.007387
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measure of transmission characteristics of low-frequency surface plasmon polaritons in frequency and time domains

Abstract: In this work, based on the use of the concept of spoof surface plasmon polaritons (spoof SPPs), we propose a novel kind of microstrips to suppress the interference between bended parallel microstrips. This novel structure is implemented by introducing subwavelength periodic structures onto the sides of a conventional microstrip. We numerically analyze the transmission characteristics of such new microstrips. We also measure the suppression arising from crosstalk between the bended corrugated microstrip and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Compared to the previously reported works, [33][34][35][36] the proposed UCSSPP TL has a narrower linewidth and can achieve better crosstalk suppression performance at a smaller separation, as summarized in Table 1.…”
Section: Analysis Of the Signal Integritymentioning
confidence: 92%
See 1 more Smart Citation
“…Compared to the previously reported works, [33][34][35][36] the proposed UCSSPP TL has a narrower linewidth and can achieve better crosstalk suppression performance at a smaller separation, as summarized in Table 1.…”
Section: Analysis Of the Signal Integritymentioning
confidence: 92%
“…Thanks to the strong confinement characteristics of SSPPs, they have naturally exhibited unique advantages in crosstalk suppression. [33][34][35][36] However, most of the previously reported works either have a complicated double-layer structure that is difficult to be compatible with the conventional MS circuits or have wide linewidth that is not conducive to the design of highly integrated circuits. Hence, the development of TL with narrow linewidth and good signal integrity can realize the miniaturization of devices and greatly improve the degree of integration of planar circuits.…”
Section: Introductionmentioning
confidence: 99%
“…This is a severe challenge to miniaturization of circuit area. This isolation method is not very effective in the case of higher frequencies [18]. Generally speaking, for two conventional coupled microstrip lines, the ratio of mutual capacitance to self-capacitance is smaller than the ratio of mutual inductance to self-inductance, which leads directly to a greater FEXT.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the separation distance greatly influences the S $S$‐parameters between two microstrip lines, and it may generate a resonant coupling effect when an inappropriate separation distance is chosen. However, with the increasing signal frequency, the spacing rules and the grounded guard trace are no longer effective in crosstalk suppressing [16]. The above two isolation methods involve at least three times the microstrip line width, which will lead to serious difficulties in reducing the circuit area.…”
Section: Introductionmentioning
confidence: 99%